Implementation of Tolerance Character Education: A Comparative Study of Indonesian and Japanese Elementary Schools - Imama, Nur Hasanah Al; Hidayat, Muhamad Taufik (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This study examines and compares the integration of tolerance-based character education among elementary school students in Indonesia and Japan. Methodology: A qualitative approach is employed in this research, utilising a methodological literature review framework. Specifically, a comparative literature review design is adopted. The data for this study are sourced from online journal articles and website publications. Three techniques are employed to ensure data validity: researcher persistence, cross-validation with other researchers, and source triangulation. Data analysis involves processes of data reduction, presentation, and conclusion. Results: The findings illustrate similarities and distinctions in implementing tolerance-based character education within Indonesian and Japanese elementary schools. Shared elements include (1) the encouragement of individual belief systems, (2) the promotion of respect for diversity and the fostering of open-mindedness, (3) the rejection of discriminatory behaviour, and (4) the cultivation of empathy and the establishment of communal bonds. Conversely, differences emerge in practices such as (1) Japanese students consistently bowing in respect or gratitude, a custom not prevalent in Indonesian elementary schools, and (2) Japanese elementary students commuting to school independently, in contrast to Indonesian counterparts whose parents often accompany. Applications/Originality/Value: This study compares tolerance-based character education implementation in Indonesian and Japanese elementary school settings. It represents a pioneering exploration specifically addressing the comparative aspects of tolerance character development in these educational contexts.